The Impact of COVID-19 on Social Work Practice in Canada: A Comparison of Urban and Rural Contexts - Baker, Matthew; Berens, Katie A.; Williams, Shanna; Bruer, Kaila C.; Evans, Angela D.; Price, Heather L. (Journal of Comparative Social Work, 2021)
Social workers involved in child maltreatment investigations faced considerable challenges during the COVID-19 pandemic. Interactions with children and families carried new restrictions and risks, which resulted in changes in practice. We conducted a two-phase, mixed-methods study which examined the impact of the COVID-19 pandemic on social workers who work with maltreated children from both urban and rural areas across Canada. More specifically, we examined changes in service delivery, as well as perceptions of safety, stress, worry, and how support differed between urban and rural social workers. Fifty social workers (62% urban, 38% rural) responded to the Phase 1 survey, disseminated in May 2020, with 34 (76% urban, 24% rural) responding to the Phase 2 survey in November 2020. Quantitative and qualitative data revealed that rural social workers reported more worry, stress and a greater need for mental health support, in addition to receiving less support than urban social workers during the first wave of COVID-19 cases. However, during the second wave of cases, urban social workers reported more stress, a greater need for mental health support, and receiving less support than rural social workers. Additional research is needed to further uncover the nature of the differences between rural and urban social workers, and to identify the prolonged effects of the COVID-19 pandemic on social workers.